PENINGKATAN KEMAMPUAN BERBICARA MELALUI MEDIA TEROPONG KERTAS PADA SISWA KELOMPOK A RA PERWANIDA PINGGIRSARI - Zian Alfiana (Madaris: Jurnal Guru Inovatif, 2021)
This study aims to determine the improvement of speaking skills through the binocular method of group A students RA Perwanida Pinggirsari Ponorogo. This research is a classroom action research using a cycle model consisting of two cycles, each of which includes action planning, observation, evaluation, and reflection. The subjects of this study were 18 children of group A RA Perwanida Pinggirsari. The data collection technique uses observation, test, performance, and assignment techniques. Data analysis techniques used data reduction, data presentation, and data verification. The results showed an increase in the ability to speak through paper binoculars. This can be shown by the increasing ability of children from before and after the action. In the first cycle shows an increase in speaking ability with the percentage of children who reach the Very Well Developed category, namely 50% (9 children out of 18 children). In cycle II, it shows an increase in speaking ability with the percentage of children who reach the Very Well Developed (BSB) category, which is 83.33% (15 children out of 18 children).